Medico-Legal Cases Registered in the Casualty Department of a Teaching Hospital in Nepal (Nepal Medical College Journal, 2022)
Medico-Legal Case (MLC) refers to any case of injury or ailment where some criminality is involved. The injury cases suggestive of criminal offense, burn injuries, vehicular accidents, suspected homicide, poisoning, and sexual assault are medico-legal cases. We conducted a descriptive study in Casualty Department of Teaching Hospital, Kathmandu, Nepal from May 1, 2019 to October 31, 2020. A total of 487 cases were registered. The cases were categorized according to the type of treatment they required. The record was obtained after informed consent of participants and with due assurance of confidentiality, ethical regulations and repute of the institution and individual. The data obtained was analyzed in SPSS version 21. Out of the total, 317 were male and 170 were female. The highest recorded cases were due to road traffic accidents (RTA) accounting for 167 (34.3%). The second highest was physical assault comprising 146 cases (30%) followed by fall injury 81 cases (16.6%). The study showed 48 poisoning cases (9.6%), followed by 14 cases (2.9%) of electric shock. Alcohol intoxication and trauma were eight (1.6%) each. Similarly, suicide and blast cases were six (1.2%) each. Likewise, occupational hazard and sexual assault were found one (0.2%) each, during this study period. The most common age group for medico-legal cases was 21-30 years and above 60 years were the least common. RTAs account the major part of Medico-legal cases in our study. By imparting proper education and awareness among public and medical students the frequency of these cases can be reduced.